A sustainable, continuously expandable, wearable breath moisture-induced electricity generator. (July 2022) - Chen, Si; Xia, Hong; Ni, Qing-Qing
Abstract: Moisture from the breath is a ubiquitous water energy source. The inability to continuously provide water molecules limits its application in moisture-induced electricity generation. This study first develops an electricity-sustainable breath-moisture-induced electricity generator (BMIEG) during intermittent exhalations. The generator is fabricated by the end-to-end connection of two equal asymmetric regional sandwich structural graphene oxide/carbon nanotube based composite films, making it continuously expandable without limit. The BMIEG presents a slow discharging behavior when exhalation is stopped, and it continually lights up a light-emitting diode in the intermittent exhalation process with a simple size expansion of a series of array arrangements. Additionally, the BMIEG is freely assembled using a capacitor to achieve variable voltage and/or stabilized voltage electricity supply. The flexibility and reusability of the generator show its considerable application prospects in wearable electronic products. Graphical abstract: Image 1 Highlights: A regionally sandwich structural GO/CNT based composite film for use. A dual-drive generator mechanism based on the regional hydrophilicity differences. A wearable electricity generator can continuously supply power under exhalations.